Reactions to Crime in Atlanta and Chicago, 1979-1980 - Spelman, William ([Verlag nicht ermittelbar], 1985)
Two previously released data collections from ICPSR are combined in this dataset: CHARACTERISTICS OF HIGH AND LOW CRIME NEIGHBORHOODS IN ATLANTA, 1980 (ICPSR 7951) and CRIME FACTORS AND NEIGHBORHOOD DECLINE IN CHICAGO, 1979 (ICPSR 7952). Information for ICPSR 7951 was obtained from 523 residents interviewed in six selected neighborhoods in Atlanta, Georgia. A research team from the Research Triangle Institute sampled and surveyed the residents. ICPSR 7952 contains 3,310 interviews of Chicago residents in eight selected neighborhoods. The combined data collection contains variables on topics such as residents' demographics and socioeconomic status, personal crime rates, property crime rates, neighborhood crime rates, and neighborhood characteristics. The documentation contains three pieces of information for each variable: variable reference numbers for both the Atlanta and Chicago datasets, the complete wording of the questions put to the respondents of each survey, and the exact wording of the coding schemes adopted by the researchers.